Managing Migration Flows Through Foreign Aid - Léa Marchal; Claire Naiditch; Betül Simsek (University of Hamburg, Institute of Law and Economics (ILE), 2021)
This paper investigates through which channels foreign aid impacts migration to donor countries. To disentangle the non-donor-specific channels (development and credit constraint channels) from the donor-specific channels (information and instrumentation channels), we use the fact that multilateral aid is not donor-specific contrary to bilateral aid. We estimate a gravity model derived from a RUM model of migration using an IV-2SLS strategy and the DEMIG-C2C and AidData datasets. We find that aid donated by a country increases migration to that donor through an information channel and especially for the poorest recipient countries. In addition, we find that aid weakly reduces migration to any country via a development channel.
Keywords: F22; F35; O15; 330; Aid; Gravity; Migration